Structure of the H107R variant of the extracellular domain of mouse NKR-P1A at 23 Å resolution - Kolenko, Petr; Rozbeský, Daniel; Vaněk, Ondřej; Bezouška, Karel; Hašek, Jindřich; Dohnálek, Jan (Acta crystallographica. Section F, 2011)
The structure of the H107R variant of the extracellular domain of the mouse natural killer cell receptor NKR-P1A has been determined by X-ray diffraction at 2.3 Å resolution from a merohedrally twinned crystal. Unlike the structure of the wild-type receptor in space group I4(1)22 with a single chain per asymmetric unit, the crystals of the variant belonged to space group I4(1) with a dimer in the asymmetric unit. Different degrees of merohedral twinning were detected in five data sets collected from different crystals. The mutation does not have a significant impact on the overall structure, but led to the binding of an additional phosphate ion at the interface of the molecules.
Keywords: Crystallography, X-Ray; Mutation; extracelulární prostor; myši; zvířata; Protein Structure, Tertiary; mutace; Mice; Extracellular Space; Animals; lektinové receptory NK-buněk - podrodina B; molekulární modely; kvarterní struktura proteinů; NK Cell Lectin-Like Receptor Subfamily B; Protein Structure, Quaternary; Models, Molecular; terciární struktura proteinů; krystalografie rentgenová